HEALTH INSURANCE AND ITS REGULATION IN REPUBLIC OF SERBIA - Milošević, Sandra; Tepavac, Rajko (Law - Theory and Practice, 2009)
With development of economy and society, high production and economic relations are almost impossible to imagine without the insurance. With connection between goods and financial transaction and appearance of class in human society, begins a period of insurance which is, during its path of development, experienced numerous changes, but in essence its basic function remind the same- protection of persons and property. Necessity of insurance is evident and proved whit the fact that it is in constant improvement beside the character of socio-economic and political relations. Without regard to the socio-political system, basic functions of insurance remind universal and of extreme importance for each and every society. Social insurance appeared at the end of XIX century and in 1883. it was brought into Germany. After that it was accepted in Austria, Norway, Holland, Luxembourg, Finland, Hungary and England, and in XX century, in the thirties, in United States of America, Canada and in countries of South America. After the II World War social insurance became acceptable in majority countries in Africa, Asia and other parts of the world. This insurance in Serbia appeared in 1922. at the time when The Labor Law was passed. In the mean time system of social insurance was constantly improving, so today it is very different from the initial forms. Modern system of social insurance is known for protection which provides material and social security in case of health problems, lack of work capability, old age and unemployment. Basic forms of social insurance are: health insurance, disability insurance, old-age benefits and insurance in case of unemployment. This scientific work will be focusing on one aspect of social insurance – health insurance and in the way of its regulation in Republic of Serbia.